Retrofit of exterior reinforced concrete beam-column joint using pre-tensioned stiffened steel angles. (December 2022) - Ong, Chin-Boon; Chin, Chee-Loong; Ma, Chau-Khun; Tan, Jia-Yang; Awang, Abdullah Zawawi; Omar, Wahid
Abstract: This paper presents an innovative retrofit technique to strengthen the non-seismically designed reinforced concrete beam-column joint. For this purpose, five half-scale exterior beam-column joints were prepared and tested. Four of the joints were strengthened with stiffened steel angles under various pre-tensioning levels and stiffened steel angle sizes. The columns were loaded under constant axial compression, and the beams were loaded under quasi-static cyclic load. The experiment test results showed that this retrofit technique can relocate the plastic hinge from the critical joints toward beams. This improved the sudden joint shear failure mode to a ductile beam failure mode. Besides, this retrofit technique improved the seismic behaviours, including load-carrying capacity, ductility, energy dissipation, and stiffness of the beam-column joints. This paper showed that the pre-tensioning level affects the bond behaviour between the reinforcement steel and the concrete, whereas stiffened steel angle size affects the failure mode and seismic behaviours.